Enhancing quality of service in Multi-Radio Multi-Channel Wireless Mesh Networks - Raja Bongsu, Raja Hasyifah (2023)
Wireless Mesh Networks (WMNs) have rapidly evolved as cost-effective, scalable, and robust communication solutions. Multi-Radio Multi-Channel (MRMC) WMNs, in particular, have gained prominence due to their ability to meet the growing demand for wireless network services. However, they contend with interference, routing, and Quality of Service (QoS) challenges, which impede network performance. Efficient channel assignment in MRMC WMNs is dominant for ensuring high-quality wireless communication. Inadequate channel assignment can lead to interference, signal degradation, and packet loss. The Priority-based Minimum Interference Channel Assignment (PRIMICA) algorithm is introduced to address this issue. PRIMICA assigns distinct frequency channels to each radio, significantly reducing interference, packet loss, delay and ultimately enhancing QoS. PRIMICA yields impressive results, with efficient channel resource utilization leading to a 55% boost in throughput and a 54% reduction in average End-to-End Delay (EED), particularly benefiting time-sensitive traffic. Congestion reduction and optimized routing in MRMC WMNs are equally critical. These networks must effectively manage fluctuating communication traffic, signal fading, and interference. The COngestion Reduction Routing Algorithm (CORRA) tackles this challenge by evaluating link quality and interference to find optimal data paths. CORRA minimizes average delay, maximizes network throughput, and ensures QoS even in large network sizes. CORRA consistently achieves a 90% packet delivery ratio, demonstrating its collision-free scheduling, even in more extensive networks. Load-balancing and fair resource allocation present further challenges in MRMC WMNs. Striking the right balance between coverage, capacity, and interference management requires scalable load-balancing algorithms. The Load-balanced Resource Allocation (LRA) algorithm is proposed to address this challenge. LRA optimizes resource utilization, distributes network traffic evenly, and prevents overloading specific nodes or links, ultimately enhancing QoS and fairness. LRA consistently reduces delays in more extensive networks, optimizing resource utilization and maintaining low delays across various network sizes. Through extensive simulations, this research validates the effectiveness of the proposed algorithms compared to existing ones. This research utilizes the OmNET++ 4.6 simulator, an open-source tool in C++, to evaluate proposed algorithms effectively. It includes network structures, NED language for topology, and configuration files for tailored experiments. Simulation involves grid topologies and diverse conditions, using the two-ray Rayleigh model for accuracy. Ten experiments enhance statistical robustness, and specific simulation parameters ensure clear, reproducible experimental conditions. PRIMICA, CORRA, and LRA collectively contribute to improving and supporting MRMC WMNs, addressing core challenges in wireless communication networks. This research highlights the potential of these algorithms as valuable tools for network enhancement in MRMC WMNs, ensuring reliable, efficient, and high-performance data transmission.